Recreation Concept of The Chocolate Farmer Education Complex in North Kalimantan - Akbal, M; Azizah, S; Widjajanti, W W (Institut Teknologi Sepuluh Nopember, 2018)
The chocolate farmers in North Kalimantan, many do not know how and good chocolate treatment techniques, in order to get quality cocoa with high selling value. So that the resolution of the problem is by increasing the interest of the community, especially cocoa farmers, by providing attractive and comfortable containers, so that cocoa farmers can maximize the natural resources found on Sebatik island, North Kalimantan. To achieve this, the method used is to provide educational buildings, cocoa gardens, and processing facilities in one area. The process of obtaining a recreation concept in the chocolate farmers education complex includes several stages, ranging from identification, case studies, design programs and the basic concept of design. After going through these stages, a recreation concept is obtained in the form of a linear and centralized pattern of land structuring, which is a guide for visitors to access various facilities in the educational complex. It is expected that with the concept of this chocolate farmers education concept, it becomes a place of education and tourism that provides visitors with new comfort and knowledge.